IDENTIFICATION OF POTENTIAL INHIBITORS FOR LOWERING CHOLESTEROL LEVEL BY INHIBITING PCSK9 - VIKAS REDDY V,; MOURYA REDDY CH,; Suganya p, Rathi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: PCSK9 has medical significance in lowering cholesterol levels. Inhibitors target and inactivate PCSK9 in the liver. Knocking out PCSK9 (proprotein convertase subtilisin kexin 9) reduces the amount of harmful LDL cholesterol circulating in the bloodstream. There are two known inhibitors for treating the cardiovascular disease Arilocumabâ€ and Evalocumabâ€. However there are many side-effects. The current study is to identify natural and synthetic inhibitor using the pharmacophoric feature of the known inhibitor and validating the short listed candidates using Molecular dynamics and ADMET properties. Methods: Known inhibitors for the PCSK9 Protein were taken from the BINDING DATABASE. Molecular docking was performed for the known inhibitors with the PCSK9 protein. After docking the best inhibitor was selected and the docking result was then imported to find the pharmacophoric features. Results: The pharmacophore model was generated with 3 features containingÂ  1 hydrogen bond acceptor(A),1 Hydrogen bond donor(B) and 1 Aromatic ring. The constructed e-pharmacophore model was screened with more than 20000 natural compounds. 5 compounds were short listed. Among them ZINC85625485 hasÂ  glideÂ  scoreÂ  ofÂ  -13.03Â  kcal/molÂ  withÂ  glideÂ  energyÂ  wasÂ  -57.62 kcal/mol and ZINC85625406 has glide score of -8.1kcal/mol with glide energy was -39.33kcal/mol were taken as the best Hits. Conclusion: PCSK9 is known to be a therapeutic agent as it controls the plasma LDL cholesterol levels by posttranslational regulation of the LDL receptor. Therefore, up-regulation of PCSk9 can lead to elevated cholesterol level in such case inhibition of PCSK9 will be a effective remedy. In this study already known inhibitors were taken and pharmacophore feature was generated. Zinc database was screened to find out novel compounds with similar pharmacophore features that can act as potentially active compound against PCSK9. ZINC85625485 and ZINC85625406 were short listed as lead compounds with Molecular dynamics simulation and checking the ADMET properties. Â  Keywords: PCSK9, Docking, ADMET, Molecular Dynamics. Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â 